Comparative Analysis of Future Tense Expressions in English and Azerbaijani - Saadat Nuriyeva (Language, Literature and Education: Research Updates Vol. 1, 2025)
The category of tense is a verbal category. The existence of this category is universally recognized. Like all other grammatical categories, it also has its own opposemes. Belonging to different language families, the English and Azerbaijani languages differ in all the aspects (grammar, phonetics and lexis) of the language. Therefore, as non-native speakers, Azerbaijanis have many difficulties in learning English. Many scholars try to eliminate those difficulties by comparing and analyzing the languages, finding out the similarities and differences between the languages compared. One of the main problems for Azerbaijani learners of English is learning the ways of expressing futurity in English to be able to select proper means of expression while translating from English into Azerbaijani and vice versa. The development of linguistics in the last few decades has been so quick and manifold that a new insight has been implemented concerning the current problems. It gave rise to the development of the comparative typological investigation of non-kindred languages. We shall try to investigate future tense in English based upon quantitative typology that investigates this or that phenomena existing in two compared languages. Our investigation aims to show the grammatical ways of expressing the future in contemporary English, reveal similarities and differences between the ways of expressing the future in English and Azerbaijan and, consequently, provide corresponding forms in Azerbaijani. As English is much richer in the ways of expressing future action than Azerbaijani, we will analyze and provide all the possible ways of conveying them in Azerbaijani. There are many controversial and quarrel points concerning the future tense problem in English and Azerbaijani. The article highlights these problems by providing prominent linguists’ theoretical points of view as well as the author’s analysis and approach to the stated problems. The article concluded that to compensate the lack of tenses, there are many ways in the Azerbaijani language to express the corresponding forms of future action in English. All these ways should be properly delivered to the learners of English to enable them to choose the most suitable while performing English-Azerbaijani and Azerbaijani-English translations.